HEREDITARY DIFFUSE GASTRIC CANCER: GENETIC ASPECTS AND PROPHYLACTIC TOTAL GASTRECTOMY - L. N. Lyubchenko; M. G. Filippova; O. A. Anurova; P. B. Nazliev; I. S. Stilidi (Сибирский онкологический журнал)
For patients with an identified germline E-cadherin-1 (CDH1) mutation, prophylactic gastrectomy is the treatment of choice to eliminate the high risk of developing diffuse gastric  cancer. The case report describes a rare case of hereditary diffuse gastric cancer (HDGC)  associated with CDH1 gene mutation, which is reported in the Russian population for the first  time. In 2013, a 28-year- old woman was referred to Clinical Oncogenetics Laboratory with a  family history of gastric cancer. Molecular genetic analysis revealed CDH1 gene mutation. The  lifetime risk of cancer in mutation positive members is more than 80. Histological examination  of gastric biopsy specimens obtained during endoscopy revealed isolated signet ring cells in the  lamina propria. Spleenpreserving D2-lymphodissection and total gastrectomy with Roux-en-Y  reconstruction with a jejunal reservoir formation were performed at the Abdominal Oncology Surgery Department.